The Development of Financial Reporting Fraud Theory: A Systematic Literature Review - Riska Agustin Tama; Taufiq Arifin (JURNAL ECONOMINA, 2026)
This study aims to examine financial statement fraud using the fraud triangle, fraud diamond, fraud pentagon, and fraud hexagon theories in Indonesia through the Systematic Literature Review (SLR) method. This study used 23 Scopus- indexed journal articles published between 2016 and 2026. The results show that the Financial Crime journal is the most dominant journal in research, and the fraud triangle theory is the most widely used theory. The variables that most frequently influence financial statement fraud in the pressure element include financial stability, external pressure, and financial targets. In the opportunity element, there is the nature of the industry and ineffective monitoring. In the rationalization element, there is a change of auditor. In the arrogance element, there is a frequent number of CEO's pictures, and in the collusion element, there is political connections. This study highlights the importance of a deeper understanding of the dynamics of internal and external factors in fraudulent acts. This research is expected to form the basis for developing more effective internal control theories and practices to prevent financial statement fraud in the future.